UJI FISIK DAN MEKANIS PAPAN PARTIKEL BERBAHAN BAKU SABUT KELAPA DAN LIMBAH PLASTIK - Mazni Perdana; Daniel Saputra; Hersyamsi Hersyamsi (Universitas Sriwijaya, 2012)
The purpose of this study was to determine the physical and mechanical properties of particle board made from coconut fiber and plastic waste. This research used Factorial Completely Randomized Design (RALF) having two factors and each factor was consisted of three levels, whereas each treatment was replicated three times. The first treatment is the kind of plastic (A) : A1 = PET (Polietilen Tereftalat), A2 = HDPE (High Density Polyethylene), A3 = PP (Polipropilen). The second treatment is the plastic composition (B) : B1 = 50 gram, B2 = 100 gram, B3 = 150 gram. Each treatment was used same weight coconut fiber. Observed parameters were modulus of rupture, water absorption, density, swelling, and internal bonding. Based on test result of BNJD (Real Difference Distance Duncann) showed that the kind of plastic, plastic composition and their interaction had significant effect on modulus of rupture, water absorption, density and had not significant effect on swelling, and internal bonding. The combination of Polipropilen types of plastics and plastic composition 150 gram (A3B3) produced particle board having the best characteristic with rupture modulus of 5,65 N/mm2, water absorption of 92,90%, density of 326,43 Kg.m3, swelling of 2,15%, internal bonding of 0,45 N/mm2. Keywords: Particle board, plastic waste, coconut fiber